Synthesis, physical and chemical properties of 7-methylxanthine derivatives - M. I. Romanenko; O. P. Dolhikh; D. H. Ivanchenko; K. V. Aleksandrova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
It is known that 8-aminosubstituted N-methylated xanthines are dipeptidyl peptidase-4 antagonists, ligands for 5-hydroxytryptamine receptors and exert diverse biological effects. Previously, it was found that the 7-alkyl-8-piperazinoxanthines exhibit diuretic, depremic, analgesic effect. Some amino derivatives of 7-metilxanthine are promising antioxidants and 8-amino-7-ethyl-3-methylxanthine detects a distinct hypoglycemic effect.